(untitled) (Proceedings of Voronezh State University. Series: Geology, 2019)
the herpetofauna of the Stary Oskol locality includes the remains of six anurans (Pelobates sp., Bufo bufo, Pelophylax lessonae, Pelophylax ridibundus, Rana arvalis, Rana temporaria), two lizards (Anguis fragilis, cf. Lacerta agilis) and one snake (Natrix sp.). The bones of the determined forms are described. These are species with extensive habitats that currently live in the vicinity of the site. Most bones belong to forms that prefer closed biotopes, which indicates the existence of forest conditions at that time. A few finds of the bones of a spadefoot, a lake frog and a sand lizard allow us to clarify that the forest was mixed or deciduous. The climate was probably close to modern. Such herpetofauna composition could have formed under interglacial conditions, and its burial inside the second floodplain terrace makes preferred dating of the containing sediments as the Mikulin interglacial.